An Efficient and Practical System for the Synthesis of N,N-Dimethylformamide by CO2 Hydrogenation using a Heterogeneous Ru Catalyst: From Batch to Continuous Flow - Gunasekar, Gunniya Hariyanandam; Padmanaban, Sudakar; Park, Kwangho; Jung, Kwang-Deog; Yoon, Sungho (WILEY-V C H VERLAG GMBH, 2020)
In the context of CO2 utilization, a number of CO2 conversion methods have been identified in laboratory-scale research; however, only a very few transformations have been successfully scaled up and implemented industrially. The main bottleneck in realizing industrial application of these CO2 conversions is the lack of industrially viable catalytic systems and the need for practically implementable process developments. In this study, a simple, highly efficient and recyclable ruthenium-grafted bisphosphine-based porous organic polymer (Ru@PP-POP) catalyst has been developed for the hydrogenation of CO2 to N,N-dimethylformamide, which affords a highest ever turnover number of 160 000 and an initial turnover frequency of 29 000 h(-1) in a batch process. The catalyst is successfully applied in a trickle-bed reactor and utilized in an industrially feasible continuous-flow process with an excellent durability and productivity of 915 mmol h(-1) g(Ru)(-1).
Keywords: POROUS ORGANIC POLYMERS; CARBON-DIOXIDE; FORMIC-ACID; IRIDIUM COMPLEX; ALKYL FORMATES; CONVERSION; ENERGY